Explaining the isotope effect on heat transport in L-mode with the collisional electron-ion energy exchange. (11th April 2017) - Schneider, P.A.; Bustos, A.; Hennequin, P.; Ryter, F.; Bernert, M.; Cavedon, M.; Dunne, M.G.; Fischer, R.; Görler, T.; Happel, T.; Igochine, V.; Kurzan, B.; et al.
Abstract: In ASDEX Upgrade (AUG), the normalised gyroradius ρ ⋆ was varied via a hydrogen isotope scan while keeping other dimensionless parameters constant. This was done in L-mode, to minimise the impact of pedestal stability on confinement. Power balance and perturbative transport analyses reveal that the electron heat transport is unaffected by the differences in isotope mass. Nonlinear simulations with the Gene code suggest that these L-mode discharges are ion temperature gradient (ITG) dominated. The different gyroradii due to the isotope mass do not necessarily result in a change of the predicted heat fluxes. This result is used in simulations with the Astra transport code to match the experimental profiles. In these simulations the experimental profiles and confinement times are reproduced with the same transport coefficients for hydrogen and deuterium plasmas. The mass only enters in the energy exchange term between electrons and ions. These numerical observations are supported by additional experiments which show a lower ion energy confinement compared to that of the electrons. Additionally, hydrogen and deuterium plasmas have a similar confinement when the energy exchange time between electrons and ions is matched. This strongly suggests that the observed isotope dependence in L-mode is not dominated by a gyroradius effect, but a consequence of the mass dependence in the collisional energy exchange between electrons and ions.